THE CONTENT OF THE MARKET ECONOMY AND THE NECESSITY OF TRANSITION TO IT - Mixliyev Jasur Mamasadikovich (Scholar Express Journals, 2021)
A market economy is an economy based on free competition, characterized by private ownership of resources, freedom in economic activity and entrepreneurship , the use of market mechanisms in the regulation and harmonization of economic processes
Keywords: Economy; industry; liberalism; income